Effect of low and high pulsed electric field on the quality and nutritional minerals in cold boned beef M. longissimus et lumborum. (June 2017) - Khan, Ammar Ahmad; Randhawa, Muhammad Atif; Carne, Alan; Mohamed Ahmed, Isam A.; Barr, David; Reid, Malcolm; Bekhit, Alaa El-Din A.
Abstract: The present research investigated the effects of low PEF (LPEF, 2.5 kV, 200 Hz and 20 μs) and high PEF (HPEF, 10 kV, 200 Hz and 20 μs) on the quality of cold-boned beef loins at 1 and 14 days of post-treatment. HPEF increased ( P  < 0.001) the temperature of the beef M. longissimus et lumborum (LL) samples. HPEF samples had higher ( P  = 0.007) shear force than LPEF samples and control samples were not different from either. HPEF beef LL samples had higher L* values and lower a* values ( P  < 0.001) compared to LPEF and control samples. Higher lipid oxidation ( P  = 0.013) was found in HPEF samples compared to LPEF samples. Lower ( P  < 0.01) P, K and Fe concentrations were found in HPEF samples compared to LPEF samples. The results suggest that high intensity PEF treatment can negatively affect the quality of beef. Highlights: Effect of low PEF (LPEF) and high PEF (HPEF) on the quality of cold-boned beef is reported. HPEF caused sever shrinkage in cold-boned beef loins due to heat generation. Higher lipid oxidation was found in HPEF samples compared to LPEF samples. Lower P, K and Fe concentrations were found in HPEF samples compared to LPEF samples. high intensity PEF treatment can negatively affect the quality of beef.